Effects of Sodium Octanoate on Innate Immune Response of Mammary Epithelial Cells during Staphylococcus aureus Internalization. (24th December 2012) - Alva-Murillo, Nayeli; Ochoa-Zarzosa, Alejandra; López-Meza, Joel E.
Abstract : Bovine mammary epithelial cells (bMECs) are capable of initiating an innate immune response to invading bacteria. Short chain fatty acids can reduce Staphylococcus aureus internalization into bMEC, but it has not been evaluated if octanoic acid (sodium octanoate, NaO), a medium chain fatty acid (MCFA), has similar effects. In this study we determined the effect of NaO on S. aureus internalization into bMEC and on the modulation of innate immune elements. NaO (0.25–2 mM) did not affect S. aureus growth and bMEC viability, but it differentially modulated bacterial internalization into bMEC, which was induced at 0.25–0.5 mM ( ~ 60%) but inhibited at 1-2 mM ( ~ 40%). Also, bMEC showed a basal expression of all the innate immune genes evaluated, which were induced by S. aureus . NaO induced BNBD4, LAP, and BNBD10 mRNA expression, but BNBD5 and TNF- α were inhibited. Additionally, the pretreatment of bMEC with NaO inhibited the mRNA expression induction generated by bacteria which coincides with the increase in internalization; only TAP and BNDB10 showed an increase in their expression; it coincides with the greatest effect on the reduction of bacterial internalization. In conclusion, NaO exerts a dual effect on S. aureus internalization in bMEC and modulates elements of innate immune response.